Real Spectra in Logarithmic Model PT-symmetry Operators: Iso-spectra in Logarithmic PT-symmetry (European Journal of Pure and Applied Mathematics, 2023)
We reflect real spectra of new logarithmic model PT-symmetry operators with singular and non-singular in nature. We also notice the iso-spectral nature between inverted and noninverted PT-symmetry potentials. Present numerical results give good agreement with previous results.
Keywords: PT-symmetry operators; Quantum mechanics; Logarithmic Potentials